2002
DOI: 10.1002/hipo.10003
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral analysis of CREB αΔ mutation on a B6/129 F1 hybrid background

Abstract: The cyclic AMP (cAMP)-response element binding protein (CREB) is an activity-dependent transcription factor that plays a role in synaptic plasticity and memory storage in Aplysia, Drosophila, and rodents. Mice with targeted deletions of two CREB isoforms (alpha and delta; CREB alphadelta mice) have been characterized on a mixed genetic background of C57BL/6 (B6) and 129/SvEv (129), as well as on a defined F1 hybrid of B6 and FVB/N, and these results suggest that the phenotype of CREB alphadelta mice depends cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 49 publications
(62 reference statements)
8
83
0
Order By: Relevance
“…These results underscore the complexity of the genetics and transcription factor balance underlying such behaviors, as CREB-deficient mice have increased the levels of both activator and repressor CREM isoforms and given that lack of CREM leads to an apparently contrasting phenotype (Maldonado et al, 1999). In agreement with our results, mice with Creb1 aD mutation on a defined B6/129F1 background have also been reported to show anxiogeniclike responses in the elevated plus maze (Graves et al, 2002). Furthermore, a decrease in CREB function in the central amygdala has been described to be a common factor in anxiety and alcohol abuse disorders .…”
Section: ) Insupporting
confidence: 90%
See 1 more Smart Citation
“…These results underscore the complexity of the genetics and transcription factor balance underlying such behaviors, as CREB-deficient mice have increased the levels of both activator and repressor CREM isoforms and given that lack of CREM leads to an apparently contrasting phenotype (Maldonado et al, 1999). In agreement with our results, mice with Creb1 aD mutation on a defined B6/129F1 background have also been reported to show anxiogeniclike responses in the elevated plus maze (Graves et al, 2002). Furthermore, a decrease in CREB function in the central amygdala has been described to be a common factor in anxiety and alcohol abuse disorders .…”
Section: ) Insupporting
confidence: 90%
“…Other work utilizing antisense oligonucleotides has also implicated decreased CREB expression in the LC with attenuated withdrawal and electrophysiological responses (Lane-Ladd et al, 1997). On the other hand, local changes in CREB activity in the nucleus accumbens alters reactions to anxiogenic, aversive, and nociceptive stimuli Graves et al, 2002;Pandey et al, 2003;Pandey, 2003), whereas it has also been reported that the aversive properties of morphine are present in CREB mutant mice (Walters and Blendy, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Male C57BL/6J mice bred in our animal facility from mice originally obtained from The Jackson Laboratory (Bar Harbor, ME) were used in most experiments. For studies using CREB␣⌬ mutant mice, experimental mice were male and female wild-type and homozygous products of F1 crosses of CREB␣⌬ ϩ/Ϫ C57BL/6J with CREB␣⌬ ϩ/Ϫ 129/ SvEvTac mice (as by Graves et al, 2002). The CREB␣⌬ mutation (Hummler et al, 1994) had been backcrossed in a heterozygous state in each parental strain for 9 -11 generations.…”
Section: Methodsmentioning
confidence: 99%
“…The CREB␣⌬ mutation (Hummler et al, 1994) had been backcrossed in a heterozygous state in each parental strain for 9 -11 generations. Genotyping was performed as described previously (Graves et al, 2002). Cbp KIX/KIX knock-in mice were generated as described previously (Kasper et al, 2002;Wood et al, 2006) and were generously provided by Dr. Paul Brindle (St. Jude Children's Research Hospital, Memphis, TN).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation